The role of Geriatric screening tool (G8) in predicting side effect in older patients during therapy with aromatase inhibitor. Issue 2 (March 2019) - Dottorini, Lorenzo; Catena, Laura; Sarno, Italo; Di Menna, Giandomenico; Marte, Annamaria; Novelli, Eugenio; Rusca, Carmen; Bajetta, Emilio
Abstract: Background: Endocrine therapy is the main treatment in hormonosensitive breast cancer; the most frequent side effects are arthralgia, osteoporosis, depression, dyslipidemia and hypertension. G8 is a simple test developed to identify older patients who could benefit from a comprehensive geriatric assessment (CGA). The aim of this study is to evaluate the possible role of G8 in predicting side effects from treatment with aromatase inhibitor in women ≥65 years old. Matherial and method: Women ≥65 years old affected by breast cancer about to start a therapy with an aromatase inhibitor, in the adjuvant setting, were evaluated with the G8 tool. Patients were classified as "fit" with G8 score > 14 or "vulnerable" with G8 score ≤ 14; they then started treatment and clinical-instrumentalfollow-up. Results: From April 2016 to February 2018, 50 consecutive patients were screened. Median age was 75.1 (range 65–86). G8 identified 30 patients (60%) as "fit" (score > 14) and 20 (40%) as "vulnerable" (score ≤ 14). The grade of concordance between G8 score and the appearance/absence of adverse events were statistically significant (41/50 patients, 82%, p = 0.0002); sensitivity resulted in 78% and specificity was 81%; positive predictive value was 70% and negative predictive value was 87%. The most frequent adverse event was arthromyalgia. Conclusion: The G8 screening tool has a potential role in predicting side effects during a treatment with aromatase inhibitor. G8 could be very useful in everyday clinical practice for this population.